Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan - Komai, Tomoyuki (Zootaxa, 2017)
A second species of the pagurid genus Enneophyllus McLaughlin, 1997, E. ecarina n. sp., is described and illustrated on the basis of two specimens collected from the upper bathyal depths off Amami-ohshima Island, Ryukyu Islands, southern Japan. The new species is immediately distinguished from the sole known congener, E. spinirostris McLaughlin, 1997, from the Banda Sea, Indonesia, by the non-operculiform right chela and fewer ventral spiniform setae of the ambulatory dactyli. The type species of Enneophillus, E. spinirostris, was represented only by the male holotype, and examination of the female paratype of this new species enables documentation of female characteristics in the generic diagnosis. Like E. spinirostris, the new species inhabits scaphopod shells.